Forage for Thought: Mobilizing Codes in the Movement for Grass-fed Meat and Dairy Products - Weber, Klaus; Heinze, Kathryn L; DeSoucey, Michaela (Administrative Science Quarterly, 2008)
This study illuminates how new markets emerge and how social movements can effect cultural change through market creation. We suggest that social movements can fuel solutions to three challenges in creating new market segments: entrepreneurial production, the creation of collective producer identities, and the establishment of regular exchange between producers and consumers. We use qualitative data on the grassroots coalition movement that has spurred a market for grass-fed meat and dairy products in the United States since the early 1990s. Our analysis shows that the movement's participants mobilized broad cultural codes and that these codes motivated producers to enter and persist in a nascent market, shaped their choices about production and exchange technologies, enabled a collective identity, and formed the basis of the products' exchange value.